Hubungan Pengetahuan Dan Sikap Bidan Dalam Pemenuhan Kebutuhan Ibu Nifas Terhadap Konseling Keluarga Berencana (KB) Di Puskesmas Gandapura Kabupaten Bireuen Tahun 2021 - Mediana Br Sembiring; Marlina L Simbolon; Lidya Natalia Br Sinuhaji; Hayatun Nupus Sambas (Jurnal Kesehatan dan Fisioterapi, 2022)
The problem of population growth causes a lot of Maternal Mortality Rate (MMR) which is caused by uncontrolled fertility. With this problem, the Family Planning (KB) program was formed. The still weak ability of Health Human Resources in planning health services and their behavior in anticipating health problems that occur, especially family planning programs, are not in line with community expectations. This study aims to determine the relationship between knowledge and attitudes of midwives in meeting the needs of postpartum mothers on Family Planning (KB) counseling at the Gandapura Health Center, Bireuen Regency in 2021. The design used in this study was descriptive correlation with a sample size of 36 people, namely the entire population was sampled. study. This research was conducted from April 2009 to May 2009. The instrument in this research is a questionnaire which includes demographic data, knowledge questionnaire, and attitude questionnaire. The majority of midwives have sufficient knowledge as many as 24 people (66.7%) about family planning counseling, 8 people (22.2%) good knowledge about family planning counseling, and a minority of less knowledge as many as 4 people (11.1%) about family planning counseling . Based on attitudes, the majority of midwives have a positive attitude as many as 27 people (75%) about family planning counseling and a minority of negative attitudes as many as 9 people (25%) about family planning counseling. While the results of the chi square analysis with a significant value of = 0.045, it means that there is a relationship between the level of knowledge and attitudes of midwives in meeting the needs of postpartum mothers for family planning counseling (KB) at the Gandapura Health Center, Bireuen Regency. It is expected that midwives know the fulfillment of the needs of postpartum mothers in an effort to provide family planning counseling so that midwives can improve the quality and quality of contraceptive services properly.Keywords: knowledge, attitudes, postpartum mothers, family planning counseling